EVOLUTION OF SCHOOL UNIFORMS IN THE ENGLAND AND FRANCE OF THE XVI-XХ CENTURIES - Васильєва, О. С.; Пашкевич, К. Л.; Васильєва, І. В.; Колосніченко, М. В. (Art and Design, 2020)
The purpose of the article is to retrace the main stages of the formation of uniforms in European educational institutions in the XVI – XХ centuries and the transformation of such uniforms into a modern school uniform. Methodological basis of research is approach of the systems, methods comparatively – historical and art analysis. The main stages of the formation of a school uniform for boys and girls are determined. The main types of school suits of the XVI – XX centuries of England and France investigated. The conducted researches have shown that school uniforms reflected the social roles, the student’s studies. The distinctive logos of school uniform suit of countries of Europe are investigational. The origin of school uniforms for girls was also study and the features of its development in educational institutions in England and France of the XVI – XX centuries were determined. The scientific novelty is to consist in determining the main stages in the formation of school uniforms of the XVI – XX centuries of England and France and their types. The obtained results of the research can used in the training of specialists in the field of clothing design and in the design of modern collections of school uniforms based on the historical school costume of the XVI-XX centuries.